Adult friendship and wellbeing: A systematic review with practical implications - Pezirkianidis, Christos; Galanaki, Evangelia; Raftopoulou, Georgia; Moraitou, Despina; Stalikas, Anastassios (Frontiers in Psychology, 2023)
This study aimed to systematically review research findings regarding the relationship between adult friendship and wellbeing. A multidimensional scope for wellbeing and its components with the use of the PERMA theory was adopted. A total of 38 research articles published between 2000 and 2019 were reviewed. In general, adult friendship was found to predict or at least be positively correlated with wellbeing and its components. In particular, the results showed that friendship quality and socializing with friends predict wellbeing levels. In addition, number of friends, their reactions to their friend’s attempts of capitalizing positive events, support of friend’s autonomy, and efforts to maintain friendship are positively correlated with wellbeing. Efforts to maintain the friendship, friendship quality, personal sense of uniqueness, perceived mattering, satisfaction of basic psychological needs, and subjective vitality mediated this relationship. However, research findings highlighted several gaps and limitations of the existing literature on the relationship between adult friendship and wellbeing components. For example, for particular wellbeing components, findings were non-existent, sparse, contradictory, fragmentary, or for specific populations only. Implications of this review for planning and implementing positive friendship interventions in several contexts, such as school, work, counselling, and society, are discussed.